Effectiveness of Structured Teaching Program on Knowledge Regarding Child Sexual Abuse among Mothers in Jaypore, Khurda District, Odisha - Sonalika, Soumya (International Journal of Nursing Research, 2023)
Introduction: Child sexual abuse is a universal problem with grave life-long outcomes. The estimates vary widely depending on the country. Objectives: To assess the existing knowledge of mothers and evaluate the effectiveness of STP on knowledge of child sexual abuse. Methodology: A quantitative approach and pre experimental research design was undertaken on 60 mothers selected by convenient sampling technique. Analysis & Interpretation: 37% of mothers were in the age group26-35years.Majority (63.33%) of the mothers belong to joint family. Highest percentage (70%) of the mothers were unemployed and (45%) of the mothers had primary level education.55% mothers had no previous knowledge regarding child sexual abuse. 65% of children were going to school by walk. The knowledge level of mothers pre-test shows that 6(12%) of respondents had inadequate knowledge and 54(88%) had moderate knowledge .In post-test the majority of the respondents 47(81%) had adequate knowledge.Inareawise distributionpost test highest mean percentage is 78.5 % with mean score (4.71±1.10) for area “introduction”. The lowest mean percentage in post test is 61.2% with mean score (3.06±1.13) for area “warning signs of child molestation”.Chi square was calculated which shows no significant association between pre test scores among demographic of mothers to improve the level of knowledge score. Conclusion: Knowing the facts about child sexual abuse can help mothers for better protection of their children in life.